2014
DOI: 10.1159/000367964
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Diplopia Following Upper Blepharoplasty

Abstract: Diplopia is an infrequent complication after blepharoplasty. Most of the cases are in its vertical form due to trauma of the extraocular muscles. In this article, we present a case of horizontal diplopia following cosmetic upper blepharoplasty; we review the literature on this unexpected complication and offer some recommendations to avoid it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, the members of the American Society of Ophthalmic Plastics and Reconstructive Surgery, who responded to a survey about persistent diplopia after lower blepharoplasty, reported that they had at least one case of persistent diplopia after lower blepharoplasty with a total rate of 23.2% with all surgeons patients’ together [ 35 ]. Most cases were vertical, but there is a case report of a 61-year-old female undergoing bilateral upper blepharoplasty who developed horizontal diplopia 24 hours later [ 36 ]. There are several causes of transient diplopia, including an edematous reaction, hematoma, trauma with muscle paralysis, and muscular toxicity from local anesthesia.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the members of the American Society of Ophthalmic Plastics and Reconstructive Surgery, who responded to a survey about persistent diplopia after lower blepharoplasty, reported that they had at least one case of persistent diplopia after lower blepharoplasty with a total rate of 23.2% with all surgeons patients’ together [ 35 ]. Most cases were vertical, but there is a case report of a 61-year-old female undergoing bilateral upper blepharoplasty who developed horizontal diplopia 24 hours later [ 36 ]. There are several causes of transient diplopia, including an edematous reaction, hematoma, trauma with muscle paralysis, and muscular toxicity from local anesthesia.…”
Section: Reviewmentioning
confidence: 99%
“…Lower eyelid blepharoplasty can cause torsional diplopia if the medial and central fat pads are injured. The patient was conservatively managed until no further improvements were observed [ 36 ]. Strabismus surgery is required in refractory cases.…”
Section: Reviewmentioning
confidence: 99%